An Implementation of a Web-based Application with Personalized Learning Path and Seamless Single Sign-On for Self-paced Learning - Akira Akira; Cutifa Safitri; Ronny Juwono (President University, 2023)
Abstract—Innovation is what enables humans to thrive.History will repeat itself without innovation, and humanity’shistory is far from ideal. One thing humans do have is the choiceof a bright future. It is up to us, the future leaders, to earn andachieve this future. This is why education is so important.Education brings more innovations and wisdom to the world. Asprospective leaders, it is a must to do whatever it takes to makeeducation more accessible, enjoyable, exciting, and engaging,allowing students to feel the joy of learning as we do. Ourresearch explores methods for the system design of an e-learningplatform, focusing on integrating personalized learning pathmanagement and the seamless Single Sign-On authenticationsystem. This paper contributes to the advancement of the fieldof educational technology by proposing a solution aimed atrevolutionizing the learning experience. By proposingpersonalized learning paths and the integration of a seamlessSingle Sign-On (SSO) system, this paper addresses the criticalchallenges surrounding conventional educational approaches